Succession in brazilian family farming: a systematic literature review - Elideth Pacheco Monteiro; Cyntia Meireles Martins; Janayna Galvão de Araújo; Marcos Ferreira Brabo; Marcos Antônio Souza dos Santos (Universidade Federal do Norte do Tocantins, 2024)
The study aimed to analyze the state of Brazilian literature related to work on succession in family farming over the last 20 years, through bibliometric analysis of scientific articles, indexed in the databases Scielo, Web of Science, Scopus and Periódicos Capes. The analysis was in accordance with the PRISMA guideline, which evaluated 87 articles relevant to the topic. The studies focus mainly on the opinion of the main farmer and young farmers, and generally disregard other family members, especially women. It was observed that the South region covers 67.4% of publications, with emphasis on Rio Grande do Sul (33 articles). The articles highlight the valorization of agriculture, structured properties, diversified production, pluriactivity, young people's participation in decision-making and family support, as a stimulus for generational succession on agricultural properties, while financial difficulties, access to credit, the succession process without planning, lack of public policies, gender inequalities and lack of rural technical assistance are the main factors that negatively influence the continuity of rural activities. The study allows us to consider that family farming presents worrying difficulties and highlights the need for public policies aimed at young people, enabling social reproduction in the countryside.